Problems and Challenges of Multicultural Education in the Wana Tribe's Interior, Central Sulawesi - Fathiyah, Husna; Rosyad, Rifki (Program Studi Studi Agama-Agama Pascasarjana UIN Sunan Gunung Djati Bandung, 2025)
This study examines the importance of multicultural education in Indonesia, a country characterised by rich ethnic, religious, and cultural diversity. With a population of approximately 250 million people and over 300 ethnic groups, as well as 200 languages, this diversity can be both a blessing and a challenge if not managed properly. Multicultural education plays a crucial role in shaping national identity and fostering intercultural understanding and tolerance. However, its implementation faces various challenges, particularly in remote areas such as the Wana tribe in Central Sulawesi. Despite a strong interest in learning, limited access to education and a lack of understanding of multicultural values ​​among the younger generation pose serious problems. The research method used was descriptive, qualitative, and ethnographic, drawing on the researcher's direct experience with the local community. The results indicate that multicultural education is not only crucial for preventing social conflict but also for strengthening unity in diversity. Challenges include disparities in educational facilities and low teacher competency. Therefore, greater government attention and inclusive policies are needed to improve the quality of education and strengthen cultural identity amidst the tide of modernization.